Direct costs of both inpatient and outpatient care for all type cancers: The evidence from Beijing, China. (7th May 2019) - Yin, Xuejun; Xu, Yue; Man, Xiaowei; Liu, Liming; Jiang, Yan; Zhao, Liying; Cheng, Wei
Abstract: Background: Cancer is a major public health issue worldwide. The cost of cancer care imposes a substantial economic burden on society and patient, but it has not been thoroughly studied in China. This study aimed to describe direct cost and cost elements of all cancer types by different beneficial characteristics. Methods: The research was a retrospective observational study based on inpatient and outpatient records with a primary diagnosis of cancer from 31 hospitals in 2016. Total cost and cost per time were analyzed by cancer type, sources (prescription medicines, consumables fee for diagnosis and surgery, and other health services), and beneficial characteristics (gender and age). Results: A total of 30 224 eligible inpatient admissions and 485 391 outpatient visits were identified during the study period. Inpatient care costs account for 58.6% cancer treatment costs. Nearly 70% of the total expenditure is spent on patients aged 50‐79 years. Lung cancer had the highest economic cost (15% of overall cancer costs), followed by breast cancer (12%), and colorectal cancer (10%). Anticancer drug cost accounted a large proportion in both inpatient (37.7%) and outpatient care (64.6%). The average cost per inpatient admission was estimated to be $4590.1 (5621.9), ranging from $1157.7 (1349.8) for testis cancer to $7975 (7343.9) for stomach cancer. The regression analyses revealed that length of hospital stay, cancer type, age, payment type, and hospital level were highly correlated with the expenditure per admission ( P  < 0.001). Conclusions: The cancer care cost is substantial and varies with cancer type. Our findings provide important information for health service planning, allowing more efficient allocation of health resources for the care of people with cancer. Abstract : Distribution of cancer treatment costs by cancer type, patients' gender and cancer care.